Problems on Epigraphy and Local Theonymy in the Northwest of Spain: The Coso Dossier - Ramírez Sánchez, Manuel; González Rodríguez, Mª Cruz (Gerión. Revista de Historia Antigua, 2022)
This paper offers a refined list of all epigraphic references of the Coso theonym and its variants documented in the religious inscriptions of the early imperial period found in the conventus Lucensis and in the Spanish territory of the conventus Asturum and Bracaraugustanus. Based on te direct examination of the inscriptions, we carry out an epigraphic analysis of each epigraph. We propose to exclude five supposed mentions of this theonym considered safe to date.
Keywords: Theonymy; Local Divinities; Hispania citerior; Northwestern Spain; Conventus Lucensis; Conventus Bracaraugustanus; Conventus Asturum